A panel study of air pollution in subjects with heart failure: negative results in treated patients. Issue 5 (18th November 2008) - Barclay, J L; Miller, B G; Dick, S; Dennekamp, M; Ford, I; Hillis, G S; Ayres, J G; Seaton, A
Abstract : Objectives: To investigate preclinical adverse effects of ambient particulate air pollution and nitrogen oxides in patients with heart failure. Methods: A cohort of 132 non-smoking patients living in Aberdeen, Scotland, with stable chronic heart failure were enrolled in a repeated-measures panel study. Patients with atrial fibrillation or pacemakers were excluded. Participants were studied for 3 days every 2 months for up to 1 year with monitoring of pollutant exposure and concurrent measurements of pathophysiological responses. Measurements included daily area concentration of particulate matter with a median aerodynamic diameter of <10 micrometres (PM10 ), particle number concentration (PNC) and nitrogen oxides; daily estimated personal concentration of particulate matter with a median aerodynamic diameter of <2.5 micrometres (PM2.5 ) and PNC exposures; and 3-day cumulative personal nitrogen dioxide (NO2 ). Concurrent meteorological data were recorded. Blood was taken at the end of each 3-day block for assays of markers of endothelial activation, inflammation and coagulation. Cardiac rhythm was monitored by ambulatory Holter monitor during the final 24 h of each block. Results: The average 24 h background ambient PM10 ranged from 7.4 to 68 μg.m −3 and PNC from 454 to 11 283 particles.cm −3 . No associations were demonstrated between the incidence of arrhythmias, heart rate variability or haematological/biochemical measures and any variations in pollutant exposures at any lags. Conclusion: Assuming that low-level pollution affects the parameters measured, these findings may suggest a beneficial effect of modern cardioprotective therapy, which may modify responses to external risk factors. Widespread use of such drugs in susceptible populations may in future reduce the adverse effects of air pollution on the heart.